Ichthyofaunal Diversity of the River Indus at District Swabi, Khyber Pakhtunkhwa, Pakistan: A Baseline Study for Biodiversity Conservation and Ecological Sustainability - Waheed, Abdul; Ali, Nizar; Ahmad, Arslan; Khan, Nouman; Iqbal, Hafsa; Khan, Asma (Indus Journal of Bioscience Research, 2025)
This study investigates the ichthyofaunal diversity of the River Indus in District Swabi, Pakistan, focusing on the confluence of the River Kabul and the River Indus. The study was conducted from February to April 2024, aiming to assess fish species composition, abundance, and distribution across two sampling sites: Nabi and Jehangira. A total of 20 fish species from 10 families were identified, with Cyprinidae being the most dominant family, comprising 40% of the total specimens collected. The species diversity was higher at Jehangira (16 species) compared to Nabi (12 species), likely due to environmental factors such as water quality and sediment deposition. Environmental parameters, including water temperature (18°C to 22°C), turbidity, and flow rate, were recorded and found to influence species distribution. Species abundance was linked to seasonal variations, particularly spawning behaviors before the monsoon floods. The study also highlights the ecological impact of invasive species like Cyprinus carpio and Pangasius pangasius, which may threaten native fish populations. The findings emphasize the importance of habitat conditions and seasonal timing in understanding fish biodiversity in river ecosystems. Future research should include year-round sampling to capture broader ecological fluctuations and further investigate the impacts of invasive species on local biodiversity.